Controllable preparation of N-doped porous carbons with enhanced porosity and energy storage capacity using high internal phase emulsion template - Xue, Jiahao; Zhang, Jing; Zhao, Yulai; Cai, Jingyu; Xiao, Longqiang; Hou, Linxi (Materials chemistry and physics, 2023)
In this work, a series of N-doped porous carbons (NPCs) are prepared via high internal phase emulsion (HIPE) template, followed by growing polyaniline (PANI) arrays and subsequent carbonization/activation. As evidenced by SEM and N2 absorption/desorption results, the NPCs have interconnected hierarchical porous structures with abundant micropores and mesopores inside. The morphology and porous structures of NPCs can be tuned by changing aniline concentration and polymerization time, respectively. With the increase of aniline concentration or polymerization time, the porous structure of NPC becomes more and more serried, however too high aniline concentration (>0.75 M) makes the porous structure become sparse, which is because excess PANI will nucleate itself and make it detach from the surface of NPC. As a result, the specific surface area (SSA) of NPCs first increases to 1769 m2/g and then decreases. Electrochemical performances of the obtained NPCs are evaluated in detail. The test results indicate that both aniline concentration and polymerization time have notable influence on the specific capacitance of NPCs. The specific capacitance of NPC obtained under optimized conditions reaches up to 241 F/g at 1 A/g with a retention ratio of 97.8% after 10, 000 cycles at a high current density, proving its excellent energy storage capability and cycling stability. In two-electrode system, the NPC provides an energy density of 27 Wh/kg at a power density of 400 W/kg and remains a high energy density of 19 Wh/kg at a high power density of 10002 W/kg. [Display omitted] •N-doped porous carbons are prepared from polymer/polyaniline array composites.•N-doped porous carbons have hierarchical porous structures with high surface area.•N-doped porous carbons have high specific capacitance up to 241 F/g at 1A/g.•N-doped porous carbons show a retention ratio of 97.8% after 10, 000 cycles.•N-doped porous carbons maintain high energy density in wide power density range.